1999
DOI: 10.1063/1.477895
|View full text |Cite
|
Sign up to set email alerts
|

Effects of molecular association on mutual diffusion: A study of hydrogen bonding in dilute solutions

Abstract: Influence of solute-solvent coordination on the orientational relaxation of ion assemblies in polar solvents J. Chem. Phys. 136, 014501 (2012) Theoretical study of the aqueous solvation of HgCl2: Monte Carlo simulations using second-order Moller-Plessetderived flexible polarizable interaction potentials J. Chem. Phys. 136, 014502 (2012) A two-dimensional-reference interaction site model theory for solvation structure near solid-liquid interface J. Chem. Phys. 135, 244702 (2011) On the solvation struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 24 publications
3
43
0
Order By: Relevance
“…The uncertainty listed is the average absolute error. The reproducibility of data here is consistent with those reported in our previous works [33][34][35][36] using basically the same technique. In this study, we also report the tracer diffusivities of 1,2,4-trichlorobenzene and mesitylene in 1-butanol, which at 298.15 K are 0.730 ± 0.009 and 0.732 ± 0.008 × 10 −9 m 2 s −1 , respectively.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The uncertainty listed is the average absolute error. The reproducibility of data here is consistent with those reported in our previous works [33][34][35][36] using basically the same technique. In this study, we also report the tracer diffusivities of 1,2,4-trichlorobenzene and mesitylene in 1-butanol, which at 298.15 K are 0.730 ± 0.009 and 0.732 ± 0.008 × 10 −9 m 2 s −1 , respectively.…”
Section: Resultssupporting
confidence: 82%
“…The present results are consistent with those found previously on the diffusivities of similar solutes in other solvents. 30,[32][33][34][35] The constants a and b for systems in this and previous works, together with their respective correlation coefficients and average % deviations of fit, are given in Table II. It is noteworthy that Eq.…”
Section: A Solute Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…Similar to water, methanol molecules are able to form hydrogen bonds among themselves, which are responsible for many of the abnormal properties of bulk solvent [1][2][3]. Since the first computer simulation of liquid methanol to determine the liquid structure were carried out by Jorgensen using the Monte Carlo method [4], much of the research effort has been devoted to examining the structural and dynamic properties of methanol and aqueous solution [5][6][7][8][9][10][11][12]. The changes of structural and dynamic properties of water and aqueous solutions under the influence of an external electric field are quite important regarding electrochemistry and biology [13].…”
Section: Introductionmentioning
confidence: 99%
“…This was in accordance with the results of studies, which also found a decrease in diffusion coefficient due to the possibility of hydrogen bonding between a diffusing solute and the surrounding solvent. 18,20,21,24,29,30 Interestingly, plotting the diffusion coefficients of water in the various alkanes and alcohols ͑Fig. 4͒ did reveal a fractional power viscosity dependence as expected for the diffusion of a small solute: D ϳ −␣ .…”
Section: -5mentioning
confidence: 99%